The Effectiveness of the HIV Prevention and Control Program by the Bekasi City Health Office - Zindan, Haikal; Rifai, Maulana; Ramdani, Rachmat (Journal of Government Insight, 2025)
This study aims to evaluate the effectiveness of the HIV prevention and control program implemented by the Bekasi City Health Office. The analysis refers to Sutrisno’s (2007) indicators of program effectiveness, which include program understanding, target accuracy, timeliness, goal achievement, and tangible outcomes. A qualitative research approach was employed, using observation, interviews, and documentation as data collection techniques.The findings reveal that the HIV prevention and control program has generally been effective in its implementation. However, the goal achievement indicator has not been fully realized, as the Bekasi City Health Office has yet to meet the targets stipulated in the Ministry of Health Regulation No. 23 of 2022, Article 4(2). This research provides valuable insights and serves as an evaluation tool for improving the effectiveness of future HIV prevention and control efforts. The novelty of this study lies in its analysis of HIV-related issues in Bekasi City from the perspective of Government Science.